Conformal Coating of Powder by Initiated Chemical Vapor Deposition on Vibrating Substrate - Katrin Unger; Anna Maria Coclite (MDPI AG, 2020)
Encapsulation of pharmaceutical powders within thin functional polymer films is a powerful and versatile method to modify drug release properties. Conformal coating over the complete surface of the particle via chemical vapor deposition techniques is a challenging task due to the compromised gas-solid contact. In this study, an initiated chemical vapor deposition reactor was adapted with speakers and vibration of particles was achieved by playing AC/DC's song "Thunderstruck" to overcome the above-mentioned problem. To show the possibilities of this method, two types of powder of very different particle sizes were chosen, magnesium citrate (3-10 µm, cohesive powder) and aspirin (100-500 µm, good flowability), and coated with poly-ethylene-glycol-di-methacrylate. The release curve of coated magnesium citrate powder was retarded compared to uncoated powder. However, neither changing the thickness coating nor vibrating the powder during the deposition had influence on the release parameters, indicating, that cohesive powders cannot be coated conformally. The release of coated aspirin was as well retarded as compared to uncoated aspirin, especially in the case of the powder that vibrated during deposition. We attribute the enhancement of the retarded release to the formation of a conformal coating on the aspirin powder.